Outdoor Learning in Belgium and Türkiye: Cultural Heritage Sensitivity and Sustainability - Ilhan, Genc Osman; Tokmak, Ahmet; Aktas, Veysi (MDPI, 2025)
In educational settings, the transfer of knowledge to daily life and the permanence of learning outcomes are essential goals. In this context, Outdoor Learning (OL) has gained growing attention as an approach that connects students with real-life experiences. This study compares OL practices in T & uuml;rkiye and Belgium, examining their impact on educational sustainability and cultural heritage awareness through multiple stakeholder perspectives. Using a qualitative case study design with a holistic multiple-case approach, data were collected through field observations and semi-structured interviews conducted between January and June 2025. The research included five OL activities in T & uuml;rkiye and six in Belgium, involving students, teachers, administrators, and external observers. Data were analyzed using descriptive and content analysis. The findings show that OL fosters environmental awareness, respect for cultural heritage, local-European identity, collaboration, and responsibility, while enhancing learning retention and motivation. In Belgium, OL is implemented systematically within educational programs, whereas in T & uuml;rkiye it is expanding rapidly under new policy guidelines. However, challenges such as large class sizes, safety concerns, logistics, and financial limitations hinder consistent practice. The study concludes that OL should be organically integrated into curricula, supported by in-service teacher training and institutional financial-logistical frameworks to ensure sustainable and meaningful implementation.
Keywords: Outdoor Learning; sustainability; cultural heritage; qualitative research; comparative education; Belgium; T & uuml; rkiye; EXPERIENCES; EDUCATORS; POLICY; Science & Technology - Other Topics; Environmental Sciences & Ecology